Characterization of Enterococcus hirae isolated from the intestine of Seabass (Lates Calcarifer) as a new potential probiotic against pathogenic vibrios - Masduki, Nur Fathiah; Mohd Yaminudin, Nur Jasmin; Chong, Chou Min; Abd Karim, Murni Marlina (Springer, 2020)
In this study, we aimed to isolate, identify and characterize lactic acid bacteria (LAB) from the intestine of juvenile seabass (Lates calcarifer) as a new potential probiotic. Four strains of LABs were isolated from the intestines of ten healthy seabass juveniles. In the in vitro screening process using spot lawn assay, one isolate labeled as LAB3 showed inhibitory activity against Vibrio harveyi (ATCC 35,084). Strain LAB3 was determined to belong to the gram positive bacteria group with cocci shape and was identified as Enterococcus hirae using 16S rDNA analysis. This bacterium was able to grow at pH ranging from pH 2 to 10 with the best growth at pH 7. This strain was also able to grow at 0-4% NaCl after 24 h incubation and grew best at 1.5% NaCl. Enterococcus hirae strain LAB3 of the present study is worthy to be further characterized as a potential probiotic for use in seabass culture.